Penilaian Kinerja Layanan TI SIPP Berdasarkan ITIL: Studi Kasus Pengadilan Negeri Tasikmalaya - Nicken Syahira Anjani; Tiara Dwi Yogaputri; Rabbani Halim Natadireja; Muhammad Rabil Wahid; Helmy Dzulfikar (JUSIFOR : Jurnal Sistem Informasi dan Informatika, 2026)
This study evaluates the performance of the Information Technology services supporting the Case Tracking Information System (SIPP) at the Tasikmalaya District Court using the ITIL Service Operation framework. A qualitative interview-based approach was employed to assess incidents, service availability, and infrastructure conditions. The results show that SIPP still experiences recurring errors, system downtime, and synchronization issues, while incident handling remains reactive and undocumented. Escalation to national administrators is informal and lacks traceability, and infrastructure limitations further reduce system stability. Overall, the maturity level of IT services falls within the low-to-medium category, indicating the need for formal procedures, structured incident recording, and infrastructure improvements to enhance service reliability.